Pharmacokinetic Comparisons of Mangiferin and Mangiferin Monosodium Salt in Rat Plasma by UPLC-MS/MS - Hongbin Guo; Mengqiao Chen; Mengran Li; Mingye Hu; Baohua Chen; Chengyan Zhou (Journal of Chemistry)
Mangiferin (MG) is an active component in natural medicines, and various studies have been reported on pharmacological effects, but the low solubility and bioavailability of MG limit its wide application. The aim of the present study was to investigate the pharmacokinetic profiles of mangiferin (MG) and mangiferin monosodium salt (MG-Na) in rat plasma by UPLC-MS/MS, which were then compared between the two groups. An appropriate high sensitivity and selectivity ultraperformance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method was applied to the comparison of plasma pharmacokinetics in MG and MG-Na using carbamazepine as internal standard (IS). These results showed that there were statistically significant differences in the pharmacokinetic parameters between MG and MG-Na after a single oral administration at 100 mg/kg. When compared with pharmacokinetic parameters of MG, the AUC(0-t), AUC(0–∞), Cmax,K10, and Ka of MG-Na were increased by 5.6-, 5.7-, 20.8-, 8-, and 83.6-fold, while the Tmax and CL/F were decreased by 4- and 5.7-fold (P<0.001), respectively. t1/2 value showed an increasing trend, but was statistically significant between the two groups. Moreover, the AUC value in the MG-Na group was significantly increased and the relative bioavailability was calculated to be 570% when compared with that of the MG group. These results suggested that the salification reaction of MG can effectively enhance gastrointestinal absorption and relative bioavailability by improving solubility and membrane permeability.